1999
DOI: 10.1209/epl/i1999-00522-9
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias model for Fe/FeF 2 : Role of domains in the ferromagnet

Abstract: Exchange bias (EB) is a shift of the hysteresis loop from its normal position, symmetric around H = 0, to H E = 0. It occurs when thin ferromagnetic (F) films are deposited on a variety of antiferromagnetic (AF) materials. EB is also associated with several additional remarkable features: i) the bulk magnetizations of the F is orthogonal to the AF easy axis; ii) H E is of similar magnitude for compensated and uncompensated AF interface layers; iii) the sign of H E can assume both positive and negative values; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 31 publications
3
77
0
1
Order By: Relevance
“…The actual value of H E could then be related to the energy stored in these partial domain walls in the FM, similar to what has been suggested by some recent exchange bias models. 18 Moreover, since FM-AFM exchange bias is mainly a short-range interaction, H E tends to exponentially decrease when increasing the nonmagnetic spacer layer thickness. 4 Hence, the curves presented in Fig.…”
mentioning
confidence: 99%
“…The actual value of H E could then be related to the energy stored in these partial domain walls in the FM, similar to what has been suggested by some recent exchange bias models. 18 Moreover, since FM-AFM exchange bias is mainly a short-range interaction, H E tends to exponentially decrease when increasing the nonmagnetic spacer layer thickness. 4 Hence, the curves presented in Fig.…”
mentioning
confidence: 99%
“…The last term describes the interfacial exchange coupling with an exchange constant, J INT , between the FM and AFM spins. The parameters used in this paper are taken from previous literature [18,19]. Our simulations are carried out using a Monte Carlo method with the Metropolis algorithm [20].…”
Section: Model and Methodsmentioning
confidence: 99%
“…Moreover, Koon also showed that the magnetic moments in the AF interface layer exhibit canting; in fact, the minimum energy is achieved with the AF spins adopting a relatively small canting angle (0 < 10') relative to the AF bulk easy axis, with a component opposite to the cooling field Hld direction. However this canting, which is the manifestation of the MPE, has a significant magnitude only in the AF layer closest to the interface [21][22][23].…”
Section: Metal-insulator Fm/af Interfacesmentioning
confidence: 98%